New design of tuned vibration absorber for wide frequency range application - Ghazali, Mohd Hafiz; Zaman, Izzuddin (Asian Research Publishing Network (ARPN), 2016)
Uncontrolled vibrations can leave a bad impression to the machine, structure, and human. For example, vibration on machine can damage the equipment, decrease the machine lifetime and also causing the safety factor problems. Therefore, a vibration absorber is obliged to reduce these vibrations. The present paper investigated a new design of tuned vibration absorber (TVA). The proposed TVA is: (1) light in weight and small in scale, which suitable for mobility purpose, and (2) can addressed a broad frequency range of application. However in this paper, the effectiveness of new design of TVA to reduce the vibration is not covered since the TVA has been proved in the previous study being able to reduce the vibration significantly. The frequency range of absorber was determined through finite element analysis (FEA) and validated with the experimental result. The aim is to enhance the range of frequency that TVA can tune from 0 to 1000 Hz. In order to generate the result, SolidWorks® software was used in the finite element analysis and DEWEsoft equipment was used in experiment. The results in the finite element analysis showed that the maximum frequency that TVA can tune is 800 Hz while from experiment is 980 Hz in the experimental analysis. Although there is an error about 18% between FEA and experiment, the findings are still significant because the maximum frequency of the new design TVA can reach is approximate to 1000 Hz. This study concludes that the new design of TVA which is small in scale and light in weight is able to reduce the structural vibration extensively if it is tuned correctly to the targeted frequency range of 0 to 980 Hz.